Expression of Bifunctional Suicide Gene CDUPRT Increases Radiosensitization and Bystander Effect of 5-FC in Prostate Cancer Cells - Xing, Ligang (2009)
PURPOSE: To test a hypothesis that, with 5-fluorocytosine (5-FC) treatment, the co-expression of cytosine deaminase (CD) and uracil phosphoribosyltransferase (UPRT) can lead to greater radiosensitization and bystander effect than CD-expression alone. METHODS AND MATERIALS: R3327-AT cell lines stably expressing CD or CDUPRT were generated. The 5-FC and 5-FU cytotoxicity, and the radiosensitivity with/without 5-FC treatment, of these cells were evaluated under both aerobic and hypoxic conditions. The bystander effect was assessed by apoptosis staining and clonogenic survival. The pharmacokinetics of 5-FU and 5-FC metabolism was followed in mice bearing CD- or CDUPRT-expressing tumors using (19)F MR spectroscopy (MRS). RESULTS: CDUPRT-expressing cells were more sensitive to 5-FC and 5-FU than CD-expressing cells. CDUPRT-expression more effectively enhanced the radiosensitizing effect of 5-FC than CD-expression. A 25-fold-lower dose of 5-FC resulted in the same magnitude of radiosensitization in CDUPRT-expressing cells, relative to that in CD-expressing cells. The 5-FC cytotoxicity in co-cultures of parental cells mixed with 10–20% CDUPRT cells was similar as that in 100% CDUPRT cells. (19)F MRS measurements showed that expression of CDUPRT leads to enhanced accumulation of fluorine nucleotide (FNuc) in vivo. CONCLUSION: Our study indicates that CDUPRT/5-FC strategy may be more effective than CD/5-FC when used as an adjuvant to radiotherapy.